Consensus of Fractional-Order Multiagent Systems with Double Integrator under Switching Topologies - Shiyun Shen; Wenjing Li; Wei Zhu (Discrete Dynamics in Nature and Society)
Due to the complexity of the practical environments, many systems can only be described with the fractional-order dynamics. In this paper, the consensus of fractional-order multiagent systems with double integrator under switching topologies is investigated. By applying Mittag-Leffler function, Laplace transform, and dwell time technique, a sufficient condition on consensus is obtained. Finally, a numerical simulation is presented to illustrate the effectiveness of the theoretical result.